“THE SECURITY-DEVELOPMENT NEXUS: EVALUATING THE HUMAN SECURITY IMPACT OF THE BALEH DAM DEVELOPMENT ON THE IBAN COMMUNITY IN NANGA ENTAWAU, KAPIT, SARAWAK” - JING WEN, JONG (JONG JING WEN, 2025)
Hydropower development has emerged as a pivotal factor in advancing sustainable progress in Sarawak, epitomised by the ambitious Baleh HEP Dam project. This initiative underscores the nation's commitment to renewable energy. The primary objective of this research is to link human security and development within the security-development nexus, specifically in the context of the Baleh Hydropower Dam construction in Sarawak. This study primarily examines human and economic security using the security-development nexus framework, with a focus on the human security implications for the Iban community residing in Ulu Baleh, Kapit. By scrutinising the security-development nexus, this research explores the intricate relationship between dam development and the human and economic security of the affected community in Nanga Entawau, particularly the Iban in Baleh, Kapit. The Iban community's deep reliance on ancestral lands and rivers for sustenance and cultural identity makes them vulnerable to displacement and resource loss. The Baleh dam development has severely impacted local communities, with an estimated 1,345 square kilometres of land inundated by the dam, raising concerns about the rights and well-being of the Iban people. The findings of this research conclude that the increase in hydropower dam construction in Sarawak has led to the displacement of local communities, posing significant challenges to the human security of residents in maintaining a safe and clean environment in their villages. As these new challenges emerge, policymakers must adapt their strategies and respond effectively to ensure that development benefits local communities. This study argues that the Sarawak government needs to earnestly practice its stated commitment to sustainable development by actively engaging the affected communities. Otherwise, the government's purported sustainable development approach risks being dismissed as mere political rhetoric, further marginalising these communities and denying them active participation in their own development. Thus, this research contributes valuable insights to the ongoing discourse on security, development, and livelihood preservation, emphasizing the necessity for sustainable progress that respects the rights and interests of local communities. The findings illuminate the interrelationship between security and development,asserting that the 1,392- strong Iban community's right to a peaceful livelihood, along with their human and economic security, is closely tied to the Baleh HEP Dam in Nanga Entawau, Kapit, Sarawak.